Development of Disability Inclusion Capacity Instrument for Community Cadres: Rasch Model Analysis - Daniel Francis Hartopo; Lukman Hilfi; Mulya Nurmansyah Ardisasmita (CV Media Inti Teknologi, 2025)
Adding to their relatively high number, people with disabilities in Indonesia also face various challenges. Given such high prevalence, cadres have an important role in promoting disability inclusion. It is crucial to measure the level of knowledge, attitudes, and behaviors of these cadres regarding disability inclusion, for example, by using an instrument. To test the validity and reliability of such an instrument, statistical analysis methods like the Rasch Model Analysis are applicable due to their advantages. This study evaluates the construct validity of the Hilfi & Kaylia Disability Inclusiveness Perception instrument among health cadres. The study used a cross-sectional design using secondary data from the Disability Inclusion Capacity instrument administered to 709 cadres residing in Bandung City, Indonesia, from July to December 2024. Construct validity was analyzed using the Rasch model. Data from 626 participants who met the criteria showed that the average outfit mean-square (MnSq) for the 25-item version of the instrument met Rasch model expectations (0.92). However, item J1 was identified as a misfitting item (outfit MnSq > 1.4 and outfit Z-standard (ZSTD) > 2) across all three versions of the instrument. The explained variance was found to be 44.1%. Reliability and separation index results were excellent, with Cronbach’s alpha at 0.96 and separation index above 2. However, category response functioning and targeting did not fully meet Rasch model expectations. Nonetheless, it can be concluded that the Hilfi & Kaylia Disability Inclusiveness Perception Instrument has acceptable construct validity with the sample of health cadres in Bandung City, Indonesia.